2016
DOI: 10.1177/1357633x16633944
|View full text |Cite
|
Sign up to set email alerts
|

Can teledermatology be a useful diagnostic tool in dermatology practice in remote areas? An Egyptian experience with 600 patients

Abstract: Introduction The paucity of studies evaluating teledermatology (TD) in developing countries was the impetus behind conducting this work. We aimed to evaluate the feasibility and reliability of TD in remote areas where medical facilities and consultant dermatologists are not available, through measurement of diagnostic concordance rates between face-to-face diagnosis and store-and-forward (SAF) TD diagnosis. Methods A total of 600 patients with dermatological ailments who attended Abshway Hospital were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…34 A study conducted in a remote area in Egypt revealed 81.3% complete concordance and 97% partial/complete concordance rates, indicating that the cost-effective teleservice could enable educational programs and monitoring of practitioners. 35 Within a nonrural context, a prospective study conducted in underserved, urban primary facilities in Philadelphia revealed that teledermatology could enhance outpatient care access and clinical results in these facilities by resolving diagnostic disagreements between primary care practitioners and dermatologists. 36 For the dermatologist, clinical images of good quality have enhanced diagnostic precision.…”
Section: Diagnostic Acuity Of Teledermatological Models Along With Qumentioning
confidence: 99%
See 1 more Smart Citation
“…34 A study conducted in a remote area in Egypt revealed 81.3% complete concordance and 97% partial/complete concordance rates, indicating that the cost-effective teleservice could enable educational programs and monitoring of practitioners. 35 Within a nonrural context, a prospective study conducted in underserved, urban primary facilities in Philadelphia revealed that teledermatology could enhance outpatient care access and clinical results in these facilities by resolving diagnostic disagreements between primary care practitioners and dermatologists. 36 For the dermatologist, clinical images of good quality have enhanced diagnostic precision.…”
Section: Diagnostic Acuity Of Teledermatological Models Along With Qumentioning
confidence: 99%
“…Saleh et al 35 An analytical study was conducted in a remote area of Egypt to assess the telesystem by determining diagnostic concordance rates between face-to-face dermatologists and teledermatologists.…”
Section: Authors Setting Of Study Outcome Conclusionmentioning
confidence: 99%
“…In low-and moderate-income countries, particularly in remote areas, teledermatology has increased access, broadly defined as numbers of teledermatology encounters, as shown by studies in Afghanistan [32], 12 sub-Saharan African countries [33], and Mali [34]. Secure messaging as a vehicle for increasing teledermatology reach has been reported in Botswana [35] and Argentina [36], while a common commercial file sharing resource has been used in Egypt [37]. In Brazil, teledermatology has expanded to cover the entire state of Catarina with 83,100 completed consults from January 2014 to June 2018 [38].…”
Section: Reachmentioning
confidence: 99%
“…Im Rahmen der TD bieten sich SaF-Technologien besonders an, da sie nicht nur mit größerer Zeit-und Kostenersparnis verbunden sind [7], sondern da die meisten Hauterkrankungen gut sichtbar sind und somit gut auf Fotos abgebildet werden können, die anschließend an den Dermatologen übermittelt werden können. Vor allem in ländlichen Räumen bietet TD einige Potenziale für eine verbesserte medizinische Versorgung [7][8][9]. TD kann dabei nicht nur eine ausreichende dermatologische Versorgung in unterversorgten Gebieten sicherstellen, sondern auch die Anzahl benötigter face-to-face Termine bei Dermatologen senken und so lange Anfahrten und Wartezeiten vermeiden beziehungsweise verkürzen [10].…”
Section: Einführungunclassified